Blockchain Technology for Employment Healt Insurance Department: Adaptation Isues - Gatotrianto B; Salju; Andi Nadirah (PT Inovasi Pratama Internasional, 2023)
Blockchain technology is already being used and implemented in a number of organizational areas, including government, healthcare, banking, insurance, infrastructure, supply chain, data asset management, and education. The challenge faced by Employment BPJS is the continuation of digital technology transformation to increase membership coverage, as well as improve service quality to participants, including shortening service time. The use of a secure Blockchain system, if applied to a social security system, is of course very useful for reducing the duration of the claim process, improving data quality, reducing the risk of loss caused by human error or fraud. This research aims to identify the factors that influence organizations in adopting Blockchain technology. Next, analyze the influence of technology, organization and environment on the adoption of Blockchain technology. The population used in this study were all BPJS Ketenagakerjaan employees in 12 offices, namely 1 head office and 11 regional offices. Then, in determining the research sample, the researcher used a purposive sampling technique. The sample in this study was 150 samples. In determining the factors for adopting Blockchain technology, using the TOE framework model based on the Systematic Literature Review (SLR) with Mendeley Desktop tools to process research references. Furthermore, in a quantitative approach, data processing in this study uses Partial Least Square software (SmartPLS version 3) with a structural equation model or Structural Equation Model (SEM). The results show that technology, organization and environment have a significant and positive influence on the adoption of Blockchain technology. Likewise, the effect of adopting Blockchain technology on organizational performance. However, the organizational culture in this research model has no influence on the adoption of Blockchain technology.